PELATIHAN HOMEMADE PEPAYA SOAP BAGI KELOMPOK IBU PRODUKTIF DI KENAGARIAN SALIBUTAN KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Des M; Mades Fifendy; Elsa Yuniarti; Rezi Junialdi (Universitas Majalengka, 2021)
Nagari Salibutan has an agricultural typology. In addition to rice fields and forests, Nagari has a fairly large plantation of 500 hectares. One of the garden products produced by Nagari Salibutan is Papaya Fruit. The number of family heads in Kenagarian Salibutan is 512 families, consisting of 374 families of prosperous families and 138 families of underprivileged families. Of the number of families aged 18-56 years who are housewives as many as 42 people. So far, housewives are synonymous with taking care of the family at home, even though housewives can do other productive activities to help family income. One of the productive activities that housewives can do is make papaya soap. Harvested papayas are generally sold at a price of Rp. 2,000 to Rp. 6,000/kg. At the time of harvesting, the price of papaya tends to fall due to the abundance of papaya fruit, meanwhile there is no use of papaya fruit for direct consumption. In order for papaya fruit to have a high economic value, it is necessary to innovate to produce other selling products. One of the products produced from papaya fruit is soap. The soap produced by papaya is healthy because of the natural manufacturing process, this soap can be used as an original souvenir of the Salibutan Kenagarian. Besides that, soap from papaya fruit during the current COVID-19 pandemic, can be used by the public to wash their hands frequently. From the analysis of the situation above, the people in Kenagarian Salibutan need to be equipped with knowledge about the use of Papaya Fruits into products of economic value such as soap, so that people do not only sell papayas at low prices.